(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The article wants to offer a quick but exhaustive examination of the pictorial fragments found in the excavations of Calvatone loc. Costa Sant’Andrea in the years 1988-1998. The materials found in the so-called southern area of the excavation will be examined and then be referred to essentially two numerically and iconographically more significant groups, dating respectively to the half and the end of the first century AD.